Wildlife voluntourism : the rise with Generation Z - Bank, Marie-Louise (2021)
Voluntourism is an alternative form of tourism that involves volunteering to contribute to a community or wildlife cause. Understanding why Generation Z volunteer for wildlife projects is essential for planning and implementing strategies that take advantage of the increasingly valuable expertise and resources that volunteers bring to conservation programs. This thesis is hence essential to providing a more complete image of the factors that influence Gen Z voluntourists' attitudes and perceptions. A qualitative method including semi-structured interviews was chosen to understand the depth of the subject in its entirety. To gather sufficient and diverse perspectives on the topic, interviews were conducted with Gen Z voluntourism participants, Gen Z voluntourism non-participants, and voluntourism operators. The Leximancer program identified the primary motivators of Voluntourism as 1) volunteer-ing with 2) animals and a close interaction with them, 3) an experience that includes travel, 4) a project that benefits volunteers, tourists, and locals, and 5) a positive impact on the volunteers' lives after the project. As well as 6) the desire to contribute to the local community. As a result, the functional and theoretical consequences relate to the literature on identifying Gen Z voluntourists' key motivations.